Optimal chemotherapy treatment for patients with advanced colorectal cancer - Stec, Rafał; Bodnar, Lubomir; Smoter, Marta; Mączewski, Michał; Szczylik, Cezary (Contemporary Oncology/Współczesna Onkologia, 2011)
Colorectal cancer (CRC) is one of the most common malignancies in the world. Each year one million new cases are diagnosed and about 500 000 people die of this disease. Due to the development of research in clinical oncology, many new antineoplastic agents are registered and available in the treatment of CRC, for example irinotecan, oxaliplatin, 5-fluorouracil, capecitabine, and the monoclonal antibodies bevacizumab, panitumumab and cetuximab. Introduction of molecularly targeted therapies caused prolongation of median time to progression of the disease as well as median overall survival. The best sequence of the therapeutic options for the achievement of the patients’ benefits and good tolerance of the treatment has not been established. This article contains a review of randomized phase II/III studies and registration trials regarding systemic treatment of CRC. The authors have attempted to translate the results of the studies into treatment optimization.